Advances in virus research. - Maramorosch, Karl; Murphy, Frederick A.; Shatkin, Aaron J. (Advances in virus research, 1994)
This volume covers topics in virus research, including: new, emerging and re-emerging infectious diseases; new developments in fungal virology; developments in hepatitis delta virus research; toroviruses of humans and animals; and regulation of human immunodeficiency virus infection.